Detection of Leptospira species in environmental samples by amplification of 16S rRNA and rpoβ genes - Nurul Farhana Zulkifli,; Steffi Julan Wan,; Vasantha Kumari Neela,; Chee, Hui Yee; Siti Norbaya Masri,; Mazen M. Jamil Al-Obaidi,; Mohd Nasir Mohd Desa, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study attempted to identify and determine distribution of Leptospira spp. in environmental samples using 16S rRNA and rpoβ genes amplification. The samples were collected from high risk areas in Selangor, Malaysia. A total of 105 environmental samples consisting of soil and water were subjected to direct DNA extraction and PCR reaction. PCR products were analysed using gel electrophoresis and subjected to sequence analysis. Thirteen out of 105 (12.38%) samples were amplified for 16S rRNA with an expected amplicon size of 330 bp, while 50 out of 105 (47.62%) samples showed amplification using rpoβ primers, but were not of expected size. Of the 13 16S rRNA amplified samples, only 5 were identified as Leptospira in the gene sequence analysis and clustered under uncultured group via phylogenetic tree. This study showed the DNA-based approach using PCR and sequence analysis is able to detect the presence of Leptospira, although environmental samples may contain diverse microbial populations that may complicate the detection. Overall, the study suggested the importance of surveillance for Leptospira from environmental samples.